Analisa Kandungan Hidrokuinon Pada Krim Pemutih Wajah yang Beredar di Pasar Kodim Kota Pekanbaru Dengan Metode Spektrofotometer Uv-Vis - Kurnia Utama, Vonny; Rifqi, M. Ainur; Andini Putri, Diva (Yayasan Rahmatan Fiddunya Wal Akhirah, 2023)
Whitening cream is a type of cosmetic that incorporates active substances aimed at inhibiting the formation of melanin, thus promoting lighter skin color. Hydroquinone is a frequently utilized active compound in whitening creams, despite its potential to cause skin cancer when excessively used. The objective of this study was to determine the concentration of hydroquinone in facial whitening creams available in the Kodim Market of Pekanbaru City using the Uv-Vis Spectrophotometry method. Through spectrophotometric analysis, the following hydroquinone concentrations were obtained for the samples: sample A (3,409 ppm), sample B (4,774 ppm), sample C (3,250 ppm), sample D (7,132 ppm), and sample E (3,980 ppm). The corresponding percentages of hydroquinone content in each sample were calculated as follows: sample A (0.6818%), sample B (0.9548%), sample C (0.65%), sample D (1.4264%), and sample E (0.796%). These findings indicate that all five facial whitening creams tested contain hydroquinone.